Kompetensi Komunikasi Penyiar Di Radio Songgolangit FM Ponorogo: - Ridho, M. Hulam Mas; Dony Rano Virdaus (Jurnal Ilmu Komunikasi, 2025)
This study aims to describe and analyze the communication competence of announcers at Songgolangit FM Radio Ponorogo, including its implementation and development in broadcasting practices. The research employed a qualitative descriptive method using observation, in-depth interviews, and documentation. Data analysis followed the interactive model of Miles & Huberman, with data validation through triangulation and member checking. The findings identify six core aspects of communication competence: (1) knowledge of broadcast content, (2) announcer ethics and professionalism, (3) speaking ability, (4) program planning and creativity, (5) technological skills, and (6) interaction with listeners. Announcers play roles not only as information deliverers but also as creators of interactive and personalized listening experiences. Adaptive competence aligned with technological advancements and audience needs is key to sustaining radio.